PERSPECTIVES OF THE USE OF SEA BUCKTHORN IN THE TECHNOLOGY OF EMULSION-TYPE SAUCES - А. V. Novik (Uman National University of Horticulture, 2021)
The possibility of using dried sea buckthorn fruits in the technology of sauce preparation to increase their nutritional and biological value is considered. Rheological studies of the viscosity of the resulting mixtures were performed to determine the optimal amount of sea buckthorn powder required for the formation of oil extracts with their subsequent use in sauce preparation technologies (mayonnaise sauce). It was found that the studied additives have rheological properties similar to analog samples, which are made synthetically and added to sauces as structurants. It was found that increasing the content of sea buckthorn oil extract with a concentration of 10% in an amount of from 5 to 15% by weight of sour cream helps to stabilize the emulsion system. It was found that the use of dried sea buckthorn fruit powder as an oil extract improves the ability of macroscopic systems to self-restore the structure after its destruction. The technology of using sea buckthorn oil for making sour cream sauce was developed. Based on the IR spectroscopy of sauces with sea buckthorn oil extract, the content of proteins, carbohydrates, a large amount of fat and vitamins A and E was shown. The available set of absorption bands, which is inherent in the corresponding types of oscillations: 3400 cm-1 (phenolic oxy groups with intermolecular hydrogen bonds), 1651 cm-1 (carbonyl group of γ-pyrone); 1457 cm-1 (skeletal vibrations of aromatic rings) and 2925 cm-1 (methoxyl groups); 1645 cm-1, 1549 cm-1 and 3400 cm-1 (proteins of amide I, amide II and amide A), 2800-3000 cm-1, bands 1750 cm-1 and 1165 cm-1 with two weaker bands 1240 and 1198 cm-1 (valence vibrations of C = O groups of ester bonds of fats).